Enhancing Scientific Problem-Solving and Learning Achievement of Lower Secondary Students through Active Learning Management - Kanphukiew, S.; Nuangchalerm, P. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2024)
Active learning is an essential part of good science education. It engages students in the learning process, allowing them to get a better comprehension of scientific subjects. This research aims to enhance scientific problem-solving and also learning achievement of eighth-grade students through active learning organization. This study employed a pre-experimental design. The target group was 30 eighth-grade students from one school in Thailand. Three-hour learning management plans provided 15 hours of active learning organization. The result indicated that active learning encourages students to solve scientific problems. Students actively engage in defining and improving the learning process based on their own interests. As a result, students’ academic achievement and problem-solving in science were improved. Furthermore, when comparing the academic achievement and scientific problem-solving scores between after experiment and criterion. Additionally, students expressed a high level of satisfaction with the active science learning activities, as these activities contributed to their academic achievement and problem-solving in the field of science. It can be concluded that active learning is very useful and engage students to science classroom.